Study of a fringing field biosensor tunnel-FET - Macambira, C. N.; Agopian, P. G.D. [UNESP]; Martino, J. A. (The Electrochemical Society, 2021)
In this paper, we present a comprehensive study of the Fringing Field Biosensor Tunnel-FET (Bio-TFET) device based on 2Ddevice simulation. The presence of a biomaterial with a distinct dielectric constant (k, where ∈ = k∗∈0) on the underlap region (LUD) between gate and drain affects the ambipolar drain current (ID). The Bio-TFET can be observed in the ambipolar region (i.e., for negative gate voltage in an n type Bio-nTFET device) due to the variation of the k, biomaterial thicknesses (tBio), the LUD, and/ or the presence of charges (QBio) into the biomaterial/silicon interface. The results show that the maximum sensitivity is observed when LUD= 30 nm (3 orders of magnitude higher compared with LUDof 25 nm lower or higher than 30 nm). When tBioincreases from 10 nm to 30 nm (for k = 10), the sensitivity increases up to 1 orders of magnitude. The presence of QBiointo the biomaterial also increases the sensitivity of 60 times for a fixed value of tBio= 30 nm and k = 10 and QBiochanging from 1 × 1010cm-2to 1 × 1012cm-2. The results show that the sensitivity of the fringing field Bio-nTFET is strongly dependent on the tunneling length modulation. c 2021 The Author(s).